Starlikeness of Functions Defined by Third-Order Differential Inequalities and Integral Operators - R. Chandrashekar; Rosihan M. Ali; K. G. Subramanian; A. Swaminathan (Abstract and Applied Analysis)
Sufficient conditions are obtained to ensure starlikeness of positive order for analytic functions defined in the open unit disk satisfying certain third-order differential inequalities. As a consequence, conditions for starlikeness of functions defined by integral operators are obtained. Connections are also made to earlier known results.